Calcium Pretreated Hevea brasiliensis Sawdust for Copper Removal: Batch and Column Study - Swarup Biswas; Umesh Mishra (Journal of Chemistry)
Calcium pretreated Hevea brasiliensis sawdust has been used as an effective and efficient adsorbent for the removal of copper ion from the contaminated water. Batch experiment was conducted to check the effect of pH, initial concentration, contact time, and adsorbent dose. The results conclude that adsorption capacity of adsorbent was influenced by operating parameters. Maximum adsorption capacity found from the batch adsorption process was 37.74 mg/g at pH of 5.6. Various isotherm models like Langmuir, Freundlich, and Temkin were used to compare the theoretical and experimental data, whereas the pseudo-first-order, pseudo-second-order, and intraparticle diffusion models were applied to study the kinetics of the batch adsorption process. Dynamic studies were also conducted in packed-bed column using different bed depths and the maximum adsorption capacity of 34.29 was achieved. Characterizations of the adsorbent were done by Fourier transform infrared spectroscopy, scanning electron microscope, and energy dispersive X-ray spectroscopy.